GC-MS analysis and screening of antidiabetic, antioxidant and hypolipidemic potential of Cinnamomum tamala oil in streptozotocin induced diabetes mellitus in rats - Kumar Suresh; Vasudeva Neeru; Sharma Sunil (Cardiovascular Diabetology, 2012)
Abstract Aim of the study This study was made to investigate the antidiabetic, antioxidant and hypolipidemic potential of Cinnamomum tamala, (Buch.-Ham.) Nees & Eberm (Tejpat) oil (CTO) in streptozotocin (STZ) induced diabetes in rats along with evaluation of chemical constituents. Materials and methods The GC-MS (Gas chromatography–mass spectrometry) analysis of the oil showed 31 constituents of which cinnamaldehyde was found the major component (44.898%). CTO and cinnamaldehyde was orally administered to diabetic rats to study its effect in both acute and chronic antihyperglycemic models. The body weight, oral glucose tolerance test and biochemical parameters viz. glucose level, insulin level, liver glycogen content, glycosylated hemoglobin, total plasma cholesterol, triglyceride and antioxidant parameters were estimated for all treated groups and compared against diabetic control group. Results CTO (100 mg/kg and 200 mg/kg), cinnamaldehyde (20 mg/kg) and glibenclamide (0.6 mg/kg) in respective groups of diabetic animals administered for 28 days reduced the blood glucose level in streptozotocin induced diabetic rats. There was significant increase in body weight, liver glycogen content, plasma insulin level and decrease in the blood glucose, glycosylated hemoglobin and total plasma cholesterol in test groups as compared to control group. The results of CTO and cinnamaldehyde were found comparable with standard drug glibenclamide. In vitro antioxidant studies on CTO using various models showed significant antioxidant activity. In vivo antioxidant studies on STZ induced diabetic rats revealed decreased malondialdehyde (MDA) and increased reduced glutathione (GSH). Conclusion Thus the investigation results that CTO has significant antidiabetic, antioxidant and hypolipidemic activity.